Mahathir's leadership communication: exploring the Indians’ political and nongovernmental organisations experience - S. Maartandan Suppiah; Mohd Khairie Ahmad; Heran Niruba Gunasekaran (Penebit Universiti Kebangsaan Malaysia, 2018)
In general, there were many studies have been conducted analysing leadership communication from the majority’s group but fewer studies were conducted from the minority’s perspective. Mahathir was perceived as a leader who merely focused on the development of the majority group (Malay) and marginalised the minority communal, including the Indians. Interestingly, despite his Ultra Malay rhetoric, the Indians in Malaysia showed advancement in various sectors including politics, economics and social. Therefore, this exploratory study aims to fill in the gap by investigating the influence of Mahathir’s leadership communication from Indians political leaders and NGOs perspective in Malaysia. The transformational leadership theory was used to investigate the phenomena. In-depth interview was utilised to get an insight of the experiences of this Indians communities on Mahathir’s leadership communication. Data were collected through a series of intensive interviews with 12 informants consists of Malaysian based Indian political leaders and representatives of non-governmental organisations. Thematic analysis was used to identify, analyse and create themes from the data collected. Based on the analysis, three themes were identified; characteristics of Mahathir’s leadership communication, Mahathir as the Indian community transformer, and the expected leadership communication qualities of the Indians. This study has contributed to enhance understanding about the impacts of leadership communication from the minority community perspective. Further, it was found that the Indians are significantly affected by Mahathir’s leadership communication.